Klasični liberalizem in ideološki trki na Slovenskem - Zver, Milan (Teorija in praksa, 1999)
Classical Slovenian political differentiation in the second half of the 19th century was carried out in almost the same way as in broader European envirnoment: between liberal, catholic and social-democratic doctrines. It is interesting to notice that Slovenian liberalism was most intensively expressed in the countries, being known as catholic countries. Intense introduction of catholic political doctrine on Slovene territory led to a strong liberal reaction. Ideological tensions, following the example of German'kulturkampf', appeared firstly in the sphere of literature, but soon - already in the 1870s - immediatelly after the 'slogaštvo' period, overgrew into an intense ideological and political conflicts. The intensity of ideological confrontation was on Slovene territory due to the fact that it was carried between three antagonistic and self-sufficient bases of social organization.
Keywords: liberalism; liberalizem; socialdemokracija; katolicizem; ideologija; ideološki spori; Slovenia; Slovenija; svoboda